The Necessity of Legal Typologies in Crisis and Emergency - Johansen, Tormod Otter (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
Legal analysis necessarily uses concepts, distinctions and typologies. These tools suffer challenges when the object of analysis or application is a crisis or emergency. The article looks into two examples of legal typologies of emergencies in the works of Gross and Ní Aiolaín and Agamben respectively. Based on this four levels of analysis for legal responses to emergencies is proposed: 1) explicit descriptions of actions by actors themselves, 2) positivist legal categories available in the context, 3) meta/comparative categories, and 4) philosophical/ontological concepts and categories that question or inquire into all the previous categories. The article concludes by discussing how these levels of analysis overlaps, merge and needs to be combined in order to grasp the complex phenomena of law in crisis.